2015
DOI: 10.1016/j.jagp.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cause or Effect? Selective Serotonin Reuptake Inhibitors and Falls in Older Adults: A Systematic Review

Abstract: A 2012 update of the Beers criteria categorizes selective serotonin reuptake inhibitors (SSRIs) as potentially inappropriate medications in all older adults based on fall risk. The application of these recommendations, not only to frail nursing home residents, but also to all older adults, may lead to changes in health policy or clinical practice with harmful consequences. A systematic review of studies on the association between SSRIs and falls in older adults was conducted to examine the evidence for causati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 109 publications
1
43
0
3
Order By: Relevance
“…Our findings on the association between antidepressants use and falls or recurrent falls are also in line with results of other studies. Use of antidepressants, particularly SSRIs, has been consistently found to be associated with increased risks of falls and recurrent falls [40][41][42][43]. For example, in a longitudinal analysis of 2948 community-dwelling older adults followed-up for 7 years, antidepressant users, compared with nonusers, were observed to have a 48% greater likelihood of recurrent falls (OR 1.48, 1.12-1.96), particularly those taking SSRIs with an OR of 1.62 (1.15-2.28) [40].…”
Section: 80mentioning
confidence: 99%
“…Our findings on the association between antidepressants use and falls or recurrent falls are also in line with results of other studies. Use of antidepressants, particularly SSRIs, has been consistently found to be associated with increased risks of falls and recurrent falls [40][41][42][43]. For example, in a longitudinal analysis of 2948 community-dwelling older adults followed-up for 7 years, antidepressant users, compared with nonusers, were observed to have a 48% greater likelihood of recurrent falls (OR 1.48, 1.12-1.96), particularly those taking SSRIs with an OR of 1.62 (1.15-2.28) [40].…”
Section: 80mentioning
confidence: 99%
“…This led to consider SSRIs as potentially inappropriate in older adults with a history of falls or fractures [18]. However, two recent systematic reviews concluded that evidence of causation was lacking due to the absence of a demonstrated mediating pathway between SSRIs and falls [19] or osteoporosis [20]. As the effects of antidepressants on falls and fractures in elderly people have never been evaluated in randomized clinical trials, only well-designed analyses of large population-based cohorts can help address these relationships, evaluating long-term effects and taking into account the temporality between exposure and outcome and the main confounders.…”
Section: Introductionmentioning
confidence: 99%
“…This complicates our ability to definitively identify causal relationships between antidepressant exposure and adverse outcomes. Although observational studies can identify medication adverse events, a prerequisite is that the adverse effect is distinct from the illness [19]. This is problematic in late-life depression that is associated with a range of medical illnesses across multiple organ systems [20].…”
Section: Assessing Potential Risks In Older Populationsmentioning
confidence: 99%
“…Thus it is not always possible to disentangle what adverse health outcomes are related to antidepressant use and what are influenced by the occurrence and persistence of depression. This limits our ability to identify factors necessary to determine causality, such as temporality and specificity [19]. Moreover, conclusions from observational studies comparing depressed individuals taking antidepressants with nondepressed populations not taking antidepressants may not accurately identify true risks associated with drug exposure.…”
Section: Assessing Potential Risks In Older Populationsmentioning
confidence: 99%